Post-truth politics vs. newspaper coverage: the COVID-19 pandemic and transnational human migration in Canada, the United States and the United Kingdom - Claude Beaupre; Claude Beaupre (Frontiers in Political Science)
IntroductionIn the context of a presumed post-truth world where emotion and ideology increasingly shape public discourse, this study explores the media’s role in constructing and disseminating narratives about transnational human migration. The COVID-19 pandemic added a new layer of complexity, biologically securitizing mobility at a time when migration was already framed by xenophobia and securitization in the Western world. This study investigates how major newspapers in Canada, the United States, and the United Kingdom covered migration during the first year of the pandemic, revealing how media constructions reflected and reinforced national attitudes.MethodsA mixed-method discursive analysis was conducted on 225 articles (25 from each of nine major newspapers) from January 1 to December 31, 2020, selected for their topical relevance through the Factiva database. Articles were categorized quantitatively by topic and sentiment and qualitatively analyzed using constant comparison methods. The study focused on recurring topics, dominant narratives, and sentiment orientations (positive, neutral, neutral-negative, or negative) to identify country-specific media ‘truths’ about migration during the pandemic.ResultsDistinct national patterns emerged. Canadian newspapers exhibited largely positive or neutral portrayals of migrants, highlighting their economic and social contributions. U.S. coverage was polarized, reflecting both supportive and hostile attitudes, especially regarding Latin American migration and the Title 42 policy. U.K. articles were more frequently negative or securitized, especially concerning Channel crossings. Across all countries, themes of migrant precarity, humanitarian solidarity, and essential labor during COVID-19 were common, yet framed differently depending on national context and media sentiment.DiscussionThe findings illustrate how media in post-truth societies selectively constructed ‘truths’ about migration during a global crisis. While Canadian media maintained a largely humanitarian and pragmatic framing, U.S. and U.K. media leaned toward narratives of threat and economic burden. These constructions reflect deeper societal and political cleavages, where media act as both agents and arenas of discursive influence. The research underscores the importance of media literacy and critical discourse analysis in unpacking the role of journalism in shaping migration politics during times of uncertainty.